Intuition and «analogia entis.» Edith Stein, moderator of the dialogue between phenomenologists and scholastics - Ramos Gómez, Miriam (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The objective of this article is to offer Edith Stein’s reflections on intuition and on the analogia entis, elaborated by the author after her reading of Thomas Aquinas’ De veritate and in the context of the fundamental purpose of Steinian philosophy after her conversion to the Catholic Church on January 1st, 1922: the dialogue between phenomenology and scholasticism. We conclude by showing, first of all, that for Stein the phenomenological and scholastic sense of "intuition" are very similar. Secondly, we find that in Stein there is an ascending use of the analogy of proportionality, which places it in the Thomistic line of interpretation of the analogia entis. This use, however, has a pedagogical style that has modern interlocutors in mind and that is a reflection of the writer’s intention: to moderate the dialogue between scholastics and moderns.